Self-assessment of the provincial inspection services. Methodological proposal - Castillo García, Manuel; Ramos Corpas, Manuel Jesús; Racero Montes, Francisco José (Avances en Supervisión Educativa, 2022)
The self-assessment of educational inspectorate services is an activity that has been carried out in recent decades without previous studies or research on which organizations can rely. This paper aims to address self-assessment or internal assessment starting from the historical framework in the private and public spheres, and finally focused on self-assessment in inspection services. We developed a self-assessment model that has been piloted for years, establishing the purpose, principles, and phases of development; ending with the design of the improvement plan based on the input variables.
Keywords: educational inspection; accountability; self-evaluation; improvement plan